2021
DOI: 10.1063/5.0064455
|View full text |Cite
|
Sign up to set email alerts
|

Self-powered narrowband visible-light photodetection enabled by organolead halide perovskite CH3NH3PbBr3/p-Si heterojunction

Abstract: In this work, we have reported self-powered narrowband visible-light photodetectors based on organolead halide perovskite CH3NH3PbBr3 (MAPbBr3)/p-Si heterojunctions, which were prepared by growing MAPbBr3 microcrystals on the p-Si substrate using a room-temperature antisolvent-assisted crystallization method. Morphological, structural, and optical investigations showed that the as-grown MAPbBr3 microcrystals possessed a high crystalline quality. Electrical characterizations showed that the hetero-pn junction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In recent years, the ion migration behaviors have further been evidenced both by experimental and theoretical investigations. It was shown that halide species (Cl, Br, and I) have the lowest migration barrier height and diffuse with the assistance of grain boundaries and vacancy-type defects. ,, This results in an obvious energy band bending at both ends of the LHP film and subsequently produces the typical I – V hysteresis. For the LHP-based MSM-structured PDs, the effects of ion migration on the photodetection performance have rarely been concerned so far, although great efforts have been made previously, but they mainly focused on improving the photodetection performance of as-fabricated PDs and developing multifunctional (such as flexible, self-powered, and narrow/broad-band detection) devices. In our opinion, the effects of ion migration should be considered in the LHP-based MSM-structured PDs because a bias voltage is necessarily applied, especially for weak light detection. It is worth noting that the ion migration has been observed in the mixed halide CsPbX 3 -based light-emitting diodes recently …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the ion migration behaviors have further been evidenced both by experimental and theoretical investigations. It was shown that halide species (Cl, Br, and I) have the lowest migration barrier height and diffuse with the assistance of grain boundaries and vacancy-type defects. ,, This results in an obvious energy band bending at both ends of the LHP film and subsequently produces the typical I – V hysteresis. For the LHP-based MSM-structured PDs, the effects of ion migration on the photodetection performance have rarely been concerned so far, although great efforts have been made previously, but they mainly focused on improving the photodetection performance of as-fabricated PDs and developing multifunctional (such as flexible, self-powered, and narrow/broad-band detection) devices. In our opinion, the effects of ion migration should be considered in the LHP-based MSM-structured PDs because a bias voltage is necessarily applied, especially for weak light detection. It is worth noting that the ion migration has been observed in the mixed halide CsPbX 3 -based light-emitting diodes recently …”
Section: Introductionmentioning
confidence: 99%
“…When compared with vertical multilayered BiFeO 3 /ZnTiO 3 thin‐film structures, our devices show 1.77 times higher responsivity and ~8300 times higher τ r and τ f 19 . Compared with other standard thin‐film PDs, such as Au/CH 3 NH 3 PbBr 3 /p‐Si/Si, our devices show 4280 and 35,600 times faster τ r and τ f , respectively 20 …”
Section: Introductionmentioning
confidence: 79%
“…As described in our previous work, a 3 nm SiO x native oxide layer exists at the n-Si/ BCZT interface. 21 The BCZT layer was grown following the same procedure as that reported in our previous work 20,22 and by using a BCZT target prepared by a conventional solid-state reaction as previously described by Oliveira et al 23 The vacuum chamber was first evacuated down to a low pressure of 1 × 10 −6 mbar before the deposition. During the deposition, the substrate was maintained at a temperature of 330°C and at a distance of 87.3 mm from the target.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the built-in electric field of the heterostructure provides the driving force to effectively separate and transport the photogenerated carriers, leading to improved photodetection capability. [26][27][28][29][30][31][32] On the other hand, the depletion region generated at the interface of the heterostructure, resulting in the suppression of dark current, which is beneficial for detecting weak CPL signals. [33][34][35][36] Therefore, it would be a great opportunity for chiral perovskitebased heterostructure to achieve highly sensitive CPL detection with a low detection limit.…”
Section: Introductionmentioning
confidence: 99%